Algunas reflexiones sobre el juego como recurso e las clases de Educación Física: La justificación del juego puro - Vallejo Martín-Albo, César (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2002)
Game is the basic resource in Physical Education lessons; its advantages are obvious. Nevertheless, we often find that there are not many boys and girls who currently know "how to play". On the other hand, there is a great abuse of the word "game" in order to refer to slightly ludic activity so that we are compelled to reflect on what the "genuine game" ought to be and how it should be applied to Physical Education lessons.